Optimalisasi Peran Hakim Agung dalam Penyelesaian Perkara Kasasi dan Peninjauan Kembali - Machmudin, Dudu Duswara (Jurnal Konstitusi, 2015)
This article aims to provide knowledge and understanding on the functions of the state law enforcement agencies in Indonesia. Differences of powers and functions of law enforcement agencies such as the Supreme Court, Attorney General’s Office and the Constitutional Court needs to be understood in depth. Furthermore, given the problems in all courts all over the world which is, among others, the slow settlement of cases, this article describes and analyses the role of Supreme Court Justices in resolving cassation and review cases before and after the issuance of the decree of the Chief Justice Number 119/KMA/SK/VII/2013 regarding the determination of the Day of Deliberation and Pronouncement and Number 214/KMA/SK/XII/2104 concerning Time Period for the Handling of Cases at the Supreme Court. However, when Constitutional Court pronounced Ruling Number 34/PUU-XI/2013 a problem arises in which the products of the two state judicial bodies seem to be inconsistent, especially in the framework for the resolution of criminal cases. On the one hand, the Supreme Court wants the creation of a judicial process that is simple, speedy, and low cost through the strengthening of the two products above, but on the    other hand the Constitutional Court through its award extend the time span of litigation process for the settlement of review cases which can be done repeatedly. Thus, in order to provide legal certainty, the Supreme Court issued Supreme Court Circular Number 7 Year 2014 which essentially affirms that the petition for review in criminal cases is limited only one time based on other legal basis namely Judicial Authority Act and Supreme Court Act.